The Effect of the Rumah Belajar Portal on Critical Thinking Skills of High School Students - Mahzum, Elmi; Rezeki, Silvia; Kasli, Elisa; Saputri, Mawarni; Nasrudin, Mohammad Faidzul (Universitas Syiah Kuala, 2024)
In physics education, teachers and students have not fully utilized instructional media that can support critical thinking skills. This research aims to investigate the influence of the Home Learning Portal on the critical thinking abilities of high school students. The population of this study consists of eleventh-grade students at State Senior High School 3 Banda Aceh. The sample includes two classes, namely the experimental class and the control class, with 37 students in each class. The sample selection was conducted through simple random sampling. The research adopts a quantitative approach with an experimental research design. Data collection involves the use of test questions (pretest and posttest). Data analysis includes normality and homogeneity tests as prerequisites, and a t-test for statistical analysis. The critical thinking ability data are obtained from the percentage of indicator achievement. The results of the data analysis indicate that the obtained data are normally distributed and homogeneous. Furthermore, the t-test results show a higher score in the experimental class compared to the control class, with a calculated t-value of 4.191 the tabulated t-value of 1.666. This means that the alternative hypothesis (Ha) is accepted, concluding that there is an influence of the Home Learning Portal on the critical thinking abilities of high school students. The improvement in students' critical thinking skills is evident, with the highest average score observed in the experimental class, particularly in the conclusion indicator, at 89.19% categorized as very good.